The Seropositivity of Toxocara spp. Antibodies in Pregnant Women Attented at the University Hospital in Southern Brazil and the Factors Associated with Infection - Santos, Paula Costa (PLoS One, 2015)
BACKGROUND: Human toxocariasis is a parasitic zoonosis with a worldwide distribution but is underdiagnosed with an underestimated impact on human health. The ingestion of embryonated eggs of Toxocara spp. present on the hands or in contaminated food or water is the main mode of infection. The only record of Toxocara congenital infection in humans occurred in a premature infant. Helminth infections during pregnancy may be associated with reproductive disorders. Studies investigating the occurrence of toxocariasis in pregnancy are scarce, as is research on the possible implications of these parasites in reproductive health. The aim of this study was to determine the seroprevalence of antibodies to Toxocara spp. in pregnant women and to identify risk factors associated with its infection. METHODOLOGY/PRINCIPAL FINDINGS: The cross-sectional study of the seropositivity of specific antibodies for Toxocara spp. was performed on 280 pregnant women. Serum samples were examined with enzyme-linked immunoassay. Epidemiological data were obtained through a questionnaire containing information about obstetric history, general life style choices, and the social and economic status of the women. The prevalence of Toxocara spp. IgG in pregnant women was 6.4%. Some of the risk factors associated with the infection were owning dogs (p = 0.003), living in the city centre (p = 0.028), living at the city beach (p = 0.003), and having a family income at or below minimum wage (p < 0.001). There was no association between reproductive disorders and Toxocara seropositivity. CONCLUSIONS/SIGNIFICANCE: The seroprevalence of 6.4% for Toxocara spp. in pregnant women shows that there was exposure to the parasite. The study demonstrates the need for attention for the completion of clinical diagnosis parameters, as well as the expansion of highly specific serological studies in different regions to understand the impact of toxocariasis in pregnancy.